A The experience of parents who married as teenagers in applying discipline in child rearing: A scoping review - Eka Abelian Putri Kelana; Andari Wuri Astuti; Dewi Rokhanawati (Universitas Aisyiyah Yogyakarta, 2026)
Background: Discipline in parenting refers to actions or consequences imposed in response to rule violations. Objective: This scoping review aims to map scientific evidence related to the application of discipline, parenting experiences, and factors that influence its application in the context of families with teenage marriages. Methods: This scoping review used the five steps outlined by Arksey and O'Malley; identifying the research question, identifying relevant studies, Study Selection, data charting, results and discussion, and adhered to the prism-scr checklist. This study used the population, exposure, outcome (PEO) framework. The article searches used PubMed and Proquest databases. The critical appraisal tools used were the Joanna Briggs Institute (JBI) and Mixed Methods Appraisal Tools (MMAT). Results: The scoping review results showed that negative disciplinary practices, such as physical and emotional punishment, are still widely used in parenting, even though various studies have confirmed their adverse effects on children's psychological and emotional development. On the other hand, positive discipline is more conducive to the development of adaptive behaviour, academic ability, and warmer relationships between parents and children. Parents who marry at a young age often face considerable emotional pressure and parenting stress. The application of discipline is influenced by parental self-efficacy, family and social support, economic conditions, culture, education, and the availability of parenting resources. Conclusion: Positive discipline is a more appropriate approach.